Head injuries in children: a prospective five year follow-up. Issue 12 (December 1977) - Klonoff, H; Low, M D; Clark, C
Abstract : A five year follow-up study was conducted with two groups of head-injuried children. 131 younger than 9 years old at time of injury and 100 older than 9 years. The four aspects studied were neuropsychological function, neurological status, EEG status, and school progress. There was an extended recovery process over time, as well as evidence of a differential rate of recovery for the four aspects measured.